Plasma Phytosterol Half‐Life and Levels Are Increased in Very Low Birth Weight Preterm Infants with Parenteral Nutrition‐Associated Cholestasis. Issue 7 (6th September 2018) - Correani, Alessio; Pignotti, Azzurra; Marinelli, Luisita; Biagetti, Chiara; D'Ascenzo, Rita; Vedovelli, Luca; Verlato, Giovanna; Cogo, Paola; Rocchi, Marco B L; Carnielli, Virgilio P
Abstract: Parenteral nutrition‐associated cholestasis (PNAC) has been linked to plasma accumulation of phytosterols in infants receiving vegetable‐oil‐based lipid emulsions (LE). To date, information on the ability of infants with PNAC to metabolize intravenous (IV) phytosterols has been very limited. We characterized plasma phytosterol half‐life in very low birth weight (VLBW) preterm infants with PNAC. As part of a prospective cohort study, VLBW infants with PNAC underwent serial blood sample measurements of sitosterol (Sito), campesterol (Camp), and stigmasterol (Stigma). Infants without PNAC served as controls (CTRL, control infants). Thirty‐seven PNAC infants and 14 CTRL were studied. On PN day 7 and PN day 14, PNAC infants had higher plasma phytosterol concentrations compared to those of CTRL ( p < 0.05). A significant and positive correlation was found between plasma Camp, Stigma, Sito concentrations, and IV phytosterol intake from birth to PN day 7 ( p = 0.001, p = 0.001, and p = 0.005, respectively). Stigma concentration was positively correlated with conjugated bilirubin on PN day 7 ( p = 0.012). After stopping IV LE, half‐lives of Camp, Stigma, and Sito became significantly longer in PNAC infants than in CTRL (Camp: 18.8 ±6.2 vs 11.8 ±3.0 days, p = 0.001; Stigma: 13.8 ±5.8 vs 9.4 ±3.4 days, p = 0.023; Sito: 15.3 ±5.0 vs 9.8 ±3.0 days, p = 0.002). In conclusion, phytosterols increased earlier during PN and were eliminated slowly after stopping IV LE in PNAC infants than in CTRL. The Stigma concentration on PN day 7 could represent an early marker of cholestasis. Our results provide additional evidence on the relationship between IV phytosterols and PNAC.